From Reflections upon Professional Practice to the Design of Online Workshops on Writing - Freire, Maximina M. (The ESPecialist, 2012)
This article illustrates how reflections upon professional practice have led me to the development of a three-dimensional approach to the teaching and learning of English through online workshops on writing. It presents the findings of a previous research which support my claim that experience, reflection, and practice may provide the bases on which the skill of composing texts in English for work-related purposes can be exercised, interpreted, and improved through a series of online reflective interactions focused on the discussion of e-mail messages conveyed at work. By explaining how online workshops on writing may be designed, this article also asserts that discussing samples of e-mail messages enables professionals to interact not only with the foreign language in a unique way, but also with their own experiential continuum, thus providing them with more opportunities to perceive job activities as potential learning situations.